Shear strength generation in stabilized soils / by Anwar E.Z. Wissa and Charles C. Ladd. - Wissa, Anwar E. Z., 1935-2010.; Ladd, Charles C. (Charles Cushing); Massachusetts Institute of Technology. Department of Civil Engineering.; United States. Army Materiel Command.; U.S. Army Engineer Waterways Experiment Station. (Tufts University. Tisch Library., 2019)
1 online resource (xxviii, 290 leaves) : illustrations; "Conducted for U.S. Army Engineer Waterways Experiment Station, Vicksburg, Mississippi under Contract No. DA-22-079-eng-288."; This report is made available as part of the Dr. Charles C. Ladd Collection. For more information, contact Dr. Lewis Edgers (ledgers@tufts.edu) or Dr. Jack Germaine (john.germaine@tufts.edu) in the Tufts University Civil and Environmental Engineering department.